Early stage weathering systematics of Pb and Nd isotopes derived from a high-Alpine Holocene lake sediment record - Süfke, Finn (Chemical geology, 2019)
Radiogenic Pb and Nd isotopes are well established tools in paleoceanographic science tracing ambient climate and continental runoff to the oceans down to sub-millennial timescales. Particularly in case of Pb isotopes, a clear climate dependency of continental isotopic runoff on glacial-interglacial transitions has been observed. Pb isotopes were reported to be released incongruently during initial chemical weathering. This incongruent release implies that Pb isotopic runoff compositions differ from the bulk catchment Pb isotopic signal. Yet only little is known about the processes leading to the incongruent release and the timescales of weathering on the continents. In this study we targeted the adsorbed trace metal signature in sediments from a Swiss high-Alpine lake that have accumulated since the retreat of the large Alpine ice domes during the last deglaciation to investigate initial Pb and Nd isotope weathering processes in a granitic environment. Additionally, selected adsorbed element concentrations and ratios were analysed to complement the isotopic physico-chemical weathering information. The integrity of the presented isotope records is supported by further investigation into the lake environment (e.g. oxic/anoxic conditions) and its potential influence on the isotopic record. The Pb isotope records during the early lake phase witnessed high-amplitude isotopic fluctuations linked to the initial chemical weathering of fine glacial substrate. This finding is also supported by the lithology of the core and rapidly decreasing adsorbed Th and U concentrations. Following this early lake phase, the majority of the Holocene traced congruent release of 207Pb/204Pb and 206Pb/204Pb and a significant depletion of 208Pb/204Pb in the adsorbed phase. These findings corroborate earlier suggestions of more effective weathering of uranogenic minerals yet also call for the presence of more weathering-resistant thorogenic minerals in the lake catchment. The latest 2.2ka of the record are significantly overprinted by anthropogenic Pb deposition coinciding with the rise and fall of the Roman Empire. Finally, our data suggest that Nd isotopes are equally affected by incongruent weathering during the initial deglacial weathering processes, albeit at smaller magnitude than seen for Pb isotopes.
Gesehen am 08.08.2019